2021
DOI: 10.1111/cas.14929
|View full text |Cite
|
Sign up to set email alerts
|

Specific activation of glycolytic enzyme enolase 2 in BRAF V600E‐mutated colorectal cancer

Abstract: The BRAF V600E mutation occurs in approximately 10% of patients with metastatic colorectal cancer (CRC) and constitutes a distinct subtype of the disease with extremely poor prognosis. To address this refractory disease, we investigated the unique metabolic gene profile of BRAF V600E‐mutated tumors via in silico analysis using a large‐scale clinical database. We found that BRAF V600E‐mutated tumors exhibited a specific metabolic gene expression signature, including some genes that are associated with poor prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…The results demonstrated that NXPH4 was positively related with the top coexpressed genes (PKM2, ENO2, SLC16A3, SAPCD2, and PNCK), and all these genes were associated with poor survival of HCC. PKM, ENO2, and SLC16A3 have been researched to have important effects on promoting tumor progression [22][23][24][25][26]. Based on the GO and KEGG pathway analyses, it was suggested that the NXPH4 coexpressed genes play important roles in metabolism and intracellular signaling transduction.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that NXPH4 was positively related with the top coexpressed genes (PKM2, ENO2, SLC16A3, SAPCD2, and PNCK), and all these genes were associated with poor survival of HCC. PKM, ENO2, and SLC16A3 have been researched to have important effects on promoting tumor progression [22][23][24][25][26]. Based on the GO and KEGG pathway analyses, it was suggested that the NXPH4 coexpressed genes play important roles in metabolism and intracellular signaling transduction.…”
Section: Discussionmentioning
confidence: 99%
“…ENO2 can function as on oncogene, either in neuronal malignancies or in other cancer types, such as lung, breast, and prostate cancer [96-98]. Recent evidence was provided that the C-term domain of ENO2, which is not necessary for metabolic activity, activates the MAPK/ERK signaling pathway and thus promotes proliferation and migration of BRAV V600E-mutated CRC cells [99]. In this regard, in our study, we demonstrate that the combined knockdown of ALDOC and ENO2 signi cantly reduced lactate production and consequently attenuated the sphere-forming ability of both LUAD and breast cancer cell lines both in nutrient-rich and nutrient-restricted conditions.…”
Section: Discussionmentioning
confidence: 99%
“…ENO2 is an important member of the enolase family, which catalyzes the synthesis of phosphoenolpyruvate (PEP) to mediate glycolysis and gluconeogenesis [ 10 ]. Some studies have suggested that ENO2 promotes metastasis by activating and enhancing glycolysis [ 11 , 12 , 13 ], while others have attributed this promotion to non-glycolytic pathways [ 14 ]. Muller et al first showed that inhibition of ENO2 by the homozygous deletion of ENO1 selectively suppressed the growth and tumorigenic potential of glioblastoma cells [ 15 ].…”
Section: Introductionmentioning
confidence: 99%